Desempenho luminoso em diferentes geometrias de cozinhas: uma análise em edificações multifamiliares em Vitória - ES - Silva, Daniela Peterle (2022)
Daylighting, in addition to providing comfort and health to users, also promotes a reduction in energy consumption in buildings. In this sense, the building works code as a regulatory instrument, indicates dimensions and minimum areas to be used in an architectural project, which often does not provide luminous comfort for the user, among them, the kitchen environments. The construction code of Vitória - ES allows kitchen environments to be designed contiguous to the service areas, in which most of the time, it is the external wall of the service area that contains the opening for the access of daylighting to both environments. Therefore, the present work aims to evaluate the performance of daylighting in kitchens with different geometries in multifamily buildings in Vitória - ES. The methodology includes analysis with respect to solar geometry and simulations in TropLux 8 software, including three phases of simulations. The first phase adopts an external reflection coefficient of 0.5 and a lateral distance of 3 meters; The second phase adopts an external reflection coefficient of 0.8 and the third phase adopts a lateral distance of 6 meters. The analyzed models are kitchens of a multifamily residential building located in the urban area of the Praia do Canto neighborhood in Vitória - ES. The kitchen models have the same area and are located on the 4th, 10th, 13th and 15th floor: MC (Long Model), MR1 (Rectangular Model 1), MQ (Square Model) and MR2 (Rectangular Model 2). The simulations took place from 8:00 am to 6:00 pm in the middle of the interval on every day of the year, in the Northeast, Southeast, Southwest and Northwest orientations in dynamic sky, using 24 measurement points in the environment. In the methodology, the intervals of Useful Daylighting Illuminance (IULN), Spatial Daylighting Autonomy (ALNe), Annual Sun Exposure (ESA), Annual Mean Illuminance (EMA), Annual Mean Uniformity (UMA) and Isolux Curves were considered. As main results, it was found that the kitchen geometry made a difference in light performance, with the MC model having the worst results in all the research variables, due to its depth and the MQ and MR2 models had the best results. In addition, it was found that among all the parameters evaluated in the research, the variation of the reflectance of the external surface to, provided the best results in the light performance in the internal environment.